2023
DOI: 10.3390/jcs7100429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Modification on the Properties of Buckwheat Husk—High-Density Polyethylene Biocomposites

Roberto C. Vázquez-Fletes,
Vahid Sadeghi,
Rubén González-Núñez
et al.

Abstract: This study focuses on the production and characterization of biocomposites based on a thermoplastic polymer (high-density polyethylene, HDPE) and a biosourced filler (buckwheat husk, BHS) to develop more sustainable composites. Compounding was performed via twin-screw extrusion with three different types of BHS. In the first series, untreated BHS was directly mixed with the polymer matrix, while the second series used mercerized BHS and the third series used pretreated BHS with a coupling agent (polyethylene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The aim of the first step, which was mercerization in NaOH solution, was to activate the surface and increase the availability of hydroxyl Polymers 2024, 16, 1350 4 of 13 groups. It was performed following the procedure described by Vázquez-Fletes et al [29]. For this purpose, 50 g of ground husk was soaked in 500 mL of 5% NaOH solution at room temperature for 10 min while stirring at 400 rpm.…”
Section: Buckwheat Husk Preparation and Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the first step, which was mercerization in NaOH solution, was to activate the surface and increase the availability of hydroxyl Polymers 2024, 16, 1350 4 of 13 groups. It was performed following the procedure described by Vázquez-Fletes et al [29]. For this purpose, 50 g of ground husk was soaked in 500 mL of 5% NaOH solution at room temperature for 10 min while stirring at 400 rpm.…”
Section: Buckwheat Husk Preparation and Modificationmentioning
confidence: 99%
“…Moreover, according to Kuznetsova et al [26], buckwheat husk is a source of flavonoids and phenolic acids, which, as shown by the outcomes of previous research on the use of phenolic-rich biomass, may be beneficial for the use as the UF resin filler. This type of husk was previously used as a filler for various polymeric materials, such as polyurethane-based composites [27], polypropylene-based composites [28], polyethylene-based composites [29] and poly(lactic acid)-based composites [30], and therefore, it can be an interesting choice for formaldehyde-based resin as well.…”
Section: Introductionmentioning
confidence: 99%